Co-Benefits of Climate Change Mitigation for Public Transport in Different Cities of Vietnam - Trung Dung, Nghiem; Thi Yen Lien, Nguyen; Thu Trang, Tran; Duy Nam, Dao (VNU Journal of Science: Earth and Environmental Sciences, 2019)
Potentiality of co-benefits for public transport at cities of different grades in Vietnam namely Ho Chi Minh city (special city), Da Nang (centrally-run grade I city) and Vinh (grade I city under the province) in 2013 was studied. Taxis in Da Nang and Vinh, and buses in Ho Chi Minh City were selected for the study. A same methodology was used for all cities. In each city, three areas and nine routes in inner city were selected for conducting this study. Information on the technical conditions of vehicles was collected by questionnaires. Traffic volume was determined by vehicle counting. The real–world driving data of vehicles were recorded by GPS technology. All collected data were processed to generate input files to run IVE model associated with base state and three proposed scenarios of climate change mitigation. Emission factors (EF) of air pollutants for these transport means were determined. Co-benefits of climate, air quality and health for the scenarios in three cities were assessed. The obtained results in this study can be used as a scientific basis for integrated air quality management in the cities in general and for air pollution control of public transport in particular.  co-benefits, public transport, emission factor, IVE model, Vietnam.